2014
DOI: 10.5603/kp.a2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

The HDL paradox: what does it mean and how to manage low serum HDL cholesterol level?

Abstract: The topic of this article is an important practical lipidologic issue, along with familial hypercholesterolaemia and severe hypertriglyceridaemia which have also been recently reviewed in the Polish literature. In this paper, we attempted to summarise current scientific evidence and views on the complex role of HDL in atherogenesis, as well as therapeutic recommendations in patients with low HDL-C level. In summary, it should be noted that the available evidence does not indicate that HDL are not antiatherogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Previous studies in AMI populations have demonstrated that a lower HDL-C leads to greater mortality in both STEMI 36 and NSTEMI patients 37 . This observation may be due to the possibility of the presence of dysfunctional HDL-C, which has been described to be present in patients with coronary artery disease, obesity, diabetes mellitus and smokers 38 . It is increasingly recognized that the function and subclass of HDL-C needs to be considered above the plasma concentrations, as plasma concentrations alone cannot account for the epidemiological observations and lack of treatment efficacy when raising HDL-C levels [39][40][41] .…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies in AMI populations have demonstrated that a lower HDL-C leads to greater mortality in both STEMI 36 and NSTEMI patients 37 . This observation may be due to the possibility of the presence of dysfunctional HDL-C, which has been described to be present in patients with coronary artery disease, obesity, diabetes mellitus and smokers 38 . It is increasingly recognized that the function and subclass of HDL-C needs to be considered above the plasma concentrations, as plasma concentrations alone cannot account for the epidemiological observations and lack of treatment efficacy when raising HDL-C levels [39][40][41] .…”
Section: Discussionmentioning
confidence: 95%
“…These observations raised doubts concerning the clinical importance of CETP inhibition [31], but may also show the lack of the assumed clinical importance of an increase in HDL-C and a large reduction in LDL-C. It is also possible that such aggressive therapy may lead to non-cardiovascular mortality, secondary to still undiagnosed adverse effects [7, 19], e.g. similar to statins, which cause a dose-dependent increase in the risk of diabetes mellitus [30, 32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, better prognosis in patients with hypercholesterolemia may be related to (a) favorable effects of the “obesity paradox”: improved hemodynamic stability in the obese, adipokine protection against tumor necrosis factor-α, lipoprotein protection against endotoxins, lipophilic toxin sequestration by adipose tissue, and the modulation of inflammatory processes [10]; (b) an earlier start of contact with health care professionals; and (c) the aforementioned evidenced favorable and pleiotropic effect of hypolipidemic drugs recommended for patients with prior diagnosed hypercholesterolemia which is treated without meeting the recommended goals [13, 10]. On the other hand, the “cholesterol paradox” may be an effect of “reverse causality”, in which poor prognosis in patients with low cholesterol blood concentration results not from the lack of the aforementioned favorable effects of hyperlipidemia, but from (d) unfavorable effects of comorbidities, such as systemic inflammation, malnutrition, malabsorption syndrome, neoplasm, end-stage liver disease, end-stage kidney disease, chronic obstructive pulmonary disease (COPD), and cardiac heart failure [1518]; and/or (e) potential harmful effects of aggressive hypolipidemic therapy when hypercholesterolemia was diagnosed earlier and cholesterol was lowered too aggressively [7, 19]. Until now, the “cholesterol paradox” has been noted among geriatric patients [10] and in several acute (myocardial infarction [7, 11, 20, 21]) and chronic conditions, such as stable coronary artery disease, end-stage renal disease requiring dialysis, chronic heart failure, atrial fibrillation, peripheral artery disease, stroke, COPD, rheumatoid arthritis, and AIDS [4, 7, 13, 1418, 2227].…”
Section: Introductionmentioning
confidence: 99%
“…However, these long-established facts are contradicted by the results of clinical trials where treatment leading to an increase in HDL-C concentrations was applied and where, despite the HDL-C increase, no decrease in the rate of cardiovascular episodes was recorded. This 'HDL paradox' was recently described in Polish literature [6,7].…”
Section: Introductionmentioning
confidence: 99%